2013 IEEE International Conference on Cyber Technology in Automation, Control and Intelligent Systems 2013
DOI: 10.1109/cyber.2013.6705485
|View full text |Cite
|
Sign up to set email alerts
|

Study on hidden failure of relay protection in power system

Abstract: S tudies of major blackouts reveal that power system protection devices have contributed to a majority of system disturbances. As the most troublesome failure of relay protection, hidden failure needs more attention. In this paper, emphasis is placed on the importance of studies on hidden failure of relay protection which causes cascading failures. By clarifying the concept, characteristics and harmfulness of hidden failure, the paper proposes two response measures -vulnerability analysis and risk assessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Some utilize stochastic methods, accounting for the diversity and uncertainty of causes by varying the failure probabilities of electrical components [21−31] . Others focus on understanding specific causes, such as hidden failure models [32][33][34][35] , which explore the impact of hidden failures on cascading failures. Additionally, high-level probabilistic models aim to approximate the average influence of causes on cascading failures [36][37][38][39][40][41] .…”
Section: Causes Of Cascading Failuresmentioning
confidence: 99%
“…Some utilize stochastic methods, accounting for the diversity and uncertainty of causes by varying the failure probabilities of electrical components [21−31] . Others focus on understanding specific causes, such as hidden failure models [32][33][34][35] , which explore the impact of hidden failures on cascading failures. Additionally, high-level probabilistic models aim to approximate the average influence of causes on cascading failures [36][37][38][39][40][41] .…”
Section: Causes Of Cascading Failuresmentioning
confidence: 99%
“…By the probability model method, the hidden failure probability of a particular protection system or a particular protection scheme can be worked out under different operating conditions. So far, 4 probability models of relay protection hidden failure have been proposed: hidden failure probability model of zone III transmissionline distance protection [10,11], hidden failure probability model of over-current protection [12], hidden failure probability model of line protection considered over-flow [13], and hidden failure probability model of generator protection considered terminal-voltage [14]. The hidden failure probability value of zone III transmission-line distance protection is decided by the impedance seen by protection devices; the hidden failure probability of overcurrent protection devices is related to the magnitude of line current; the hidden failure probability of line protection considered over-flow is related to the magnitude of active line-load-flow; the hidden failure probability of generator protection considered terminal-voltage is related to the magnitude of generator's terminal voltage.…”
Section: Probability Models Of Hidden Failures Of Relay Protection Symentioning
confidence: 99%
“…Yang et al (2006) reported that hidden failure in protection system may cause multiple component outages and even spread power system disturbances. Cheng et al (2013) pointed out that hidden failure of relay protection system is the main contributor of cascading failures and blackouts.…”
Section: Introductionmentioning
confidence: 99%